CLINICAL EXAMPLE OF ITSENKO-CUSHING DRUG SYNDROME - N.A. INOYATOVA; N.F. NIYAZOVA; P.A. DAVLATOVA (Avicenna Tajik State Medical University, 2019)
The article describes a clinical example of the drug syndrome of Itsenko-Cushing in a patient suffering for 23 years of bronchial asthma and selfreceiving large doses of glucocorticoids. As a result of long-term therapy, this syndrome developed with concomitant complications such as steroid diabetes and glucocorticoid osteoporosis. In the description of this clinical example, special attention is noteworthy that complications developed as a result of therapy were regarded as a separate nosology, in particular, type 2 diabetes mellitus. It is emphasized that many specialists achieve remission simultaneously prescribe two or more glucocorticoid drugs with different duration of action without accounting for the development of the drug syndrome Itsenko-Cushing. In addition, the need for timely prevention of complications in case of inability to cancel glucocorticoid therapy is emphasized.